9 Geo. 1, c. 22 (1723), An act for the more effectual punishing wicked and evil-disposed persons going armed in disguise, and doing injuries and violences to the persons and properties of his Majesty’s subjects, and for the more speedy bringing the offenders to justice. - (:unkn) unknown (General Publisher, 1723)
Prohibited anyone going armed with sword, fire-arms, or other offensive weapons while having their faces blacked or disguised in any forest, chase, park, paddock, grounds inclosed with any wall, pale, or fence… or in any high road, open heath, common or down, or to wilfully hunt unlawfully. Violators guilty of a felony, and shall suffer death.
--
Keywords: HUNTING REGULATION